2021
DOI: 10.3390/v14010035
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Strategies Using Natural Source-Derived Sulfated Polysaccharides in the Light of the COVID-19 Pandemic and Major Human Pathogenic Viruses

Abstract: Only a mere fraction of the huge variety of human pathogenic viruses can be targeted by the currently available spectrum of antiviral drugs. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak has highlighted the urgent need for molecules that can be deployed quickly to treat novel, developing or re-emerging viral infections. Sulfated polysaccharides are found on the surfaces of both the susceptible host cells and the majority of human viruses, and thus can play an important role during v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 364 publications
0
22
0
1
Order By: Relevance
“…The use of carrageenan in nasal sprays or oral drops as a prophylactic and early-stage treatment against the common cold virus and SARS-CoV-2 is considered a very promising aspect that is currently being evaluated in several clinical trials. The current investigation results can help establish the use of polysaccharides as high-value natural antiviral drugs with low side effects (Ray et al, 2022).…”
Section: Antiviral Therapy In Covid-19mentioning
confidence: 85%
“…The use of carrageenan in nasal sprays or oral drops as a prophylactic and early-stage treatment against the common cold virus and SARS-CoV-2 is considered a very promising aspect that is currently being evaluated in several clinical trials. The current investigation results can help establish the use of polysaccharides as high-value natural antiviral drugs with low side effects (Ray et al, 2022).…”
Section: Antiviral Therapy In Covid-19mentioning
confidence: 85%
“…In the midst of a viral pandemic, fucoidan has been rapidly garnering interest for its antiviral activity [ 24 , 26 ]. Here, we analyzed global transcriptomic changes in fucoidan-treated BMDCs to better understand fucoidan’s antiviral properties.…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral effects of fucoidan have been explored in many different in vitro and in vivo infection models, including that of herpes simplex virus (HSV) [ 7 , 8 , 9 , 10 ], human immunodeficiency virus (HIV) [ 11 , 12 , 13 ], human T-lymphotropic virus type-1 (HTLV-1) [ 14 ], avian influenza virus (AIV) [ 15 ], human cytomegalovirus (HCMV) [ 16 ], Newcastle disease virus (NDV) [ 17 , 18 ], influenza virus [ 19 , 20 , 21 ], and hepatitis B virus [ 22 , 23 ]. In recent reports it has been suggested that fucoidan and other sulfated polysaccharides from seaweed have a prophylactic and therapeutic effect against SARS-CoV-2 infection [ 24 , 25 , 26 , 27 ]. While various mechanisms specific to SARS-CoV-2 have been proposed, including binding of the spike glycoprotein to prevent cell entry [ 24 , 28 ], how fucoidan exerts its effects on such a wide variety of viruses remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, marine algae are also rich in sulfated polysaccharides that prevent the replication of viruses, and they have been clinically tested, e.g., against HSV-1 [ 63 , 64 ]. Sulfated polysaccharides inhibit antiviral pathways and act as potential replication inhibitors of retroviruses such as HIV-V [ 36 ].…”
Section: Diversity Of Bioactive Metabolites and Their Potential Healt...mentioning
confidence: 99%